A high-quality human reference panel reveals the complexity and distribution of genomic structural variants - Jayne Y. Hehir-Kwa (Nature Portfolio, 2016)
Structural variants (SVs) are prevalent in genomes of the general population. Here, Guryev and The Genome of the Netherlands Consortium describe the reference panel of haplotype-resolved SVs from 769 individuals from 250 Dutch families and show its utility for studying heritable traits.